Coexistence of Pseudomonas aeruginosa With Candida albicans Enhances Biofilm Thickness Through Alginate-Related Extracellular Matrix but Is Attenuated by N-acetyl-l-cysteine - Phuengmaung, Pornpimol; Somparn, Poorichaya; Panpetch, Wimonrat; Singkham-In, Uthaibhorn; Wannigama, Dhammika Leshan; Chatsuwan, Tanittha; Leelahavanichkul, Asada (Frontiers in Cellular and Infection Microbiology, 2020)
Bacteria and Candida albicans are prominent gut-microbiota and the translocation of these organisms into blood circulation might induce mixed-organism biofilms which warrants the exploration of mixed- versus single-organism biofilms in vitro and in vivo. In single-organism biofilms, Acinetobacter baumanii and Pseudomonas aeruginosa (PA) produced the least and the most prominent biofilms, respectively. C. albicans with P. aeruginosa (PA+CA) induced the highest biofilms among mixed-organism groups as determined by crystal violet straining. Sessile form of PA+CA induced higher macrophage responses than sessile PA which supports enhanced immune activation toward mixed-organism biofilms. In addition, Candida incubated in pre-formed Pseudomonas biofilms (PA>CA) produced even higher biofilms than PA+CA (simultaneous incubation of both organisms) as determined by fluorescent staining on biofilm matrix (AF647 color). Despite the initially lower bacteria during preparation, bacterial burdens by culture in mixed-organism biofilms (PA+CA and PA>CA) were not different from biofilms of PA alone, supporting Candida-enhanced Pseudomonas growth. Moreover, proteomic analysis in PA>CA biofilms demonstrated high AlgU and mucA with low mucB when compared with PA alone or PA+CA, implying alginate-related mucoid phenotype in PA>CA biofilms. Furthermore, mice with PA>CA biofilms demonstrated higher bacteremia with more severe sepsis compared with mice with PA+CA biofilms. This is possibly due to the different structures. Interestingly, L-cysteine, a biofilm matrix inhibitor, attenuated mixed-organism biofilms both in vitro and in mice. In conclusion, Candida enhanced Pseudomonas alginate-related biofilm production and Candida presentation in pre-formed Pseudomonas biofilms might alter biofilms structures that affect clinical manifestations but was attenuated by L-cysteine.